Clinical outcomes of hepatitis C treatment in a prison setting: feasibility and effectiveness for challenging treatment populations. - Maru, Duncan Smith-Rohrberg; Bruce, Robert Douglas; Basu, Sanjay; Altice, Frederick L (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2008)
More than one-third of people in the United States with hepatic C virus (HCV) infection pass through the correctional system annually. Data are lacking on outcomes of treatment with pegylated interferon plus ribavirin (PEG-RBV) in correctional settings.
Keywords: Adult; Antiviral Agents; Drug Therapy, Combination; Female; Hepatitis C; Humans; Interferon-alpha; Longitudinal Studies; Male; Middle Aged; Polyethylene Glycols; Prisoners; Prisons; Recombinant Proteins; Retrospective Studies; Ribavirin